F-18 FDG PET/CT Findings of Primary Sinonasal Hemangiopericytoma Rare Location in a Young Adult Patient - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2011)
Hemangiopericytoma is an unusual tumor that arises from vascular smooth muscle cells. It is mainly experienced in 4th to 5th decades of life and soft-tissue masses are frequently located in lower extremity, pelvis, and retroperitoneum. A 29-year-old man presented with a mass lesion in the right nasal cavity associated with shortness of breath as a result of nasal obstruction. An incisional biopsy was reported as sinonasal type hemangiopericytoma. The initial staging F-18 flourodeoxyglucose PET/CT successfully demonstrated severe hypermetabolism in the primary tumor location and mild-to-moderate hypermetabolism in the right upper jugular lymph node.
Keywords: soft-tissue sarcoma; sinonasal hemangiopericytoma; initial staging; F-18 FDG PET/CT; TUMORS